2013
DOI: 10.1111/gcb.12384
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration potential of soils in southeast Germany derived from stable soil organic carbon saturation

Abstract: Sequestration of atmospheric carbon (C) in soils through improved management of forest and agricultural land is considered to have high potential for global CO2 mitigation. However, the potential of soils to sequester soil organic carbon (SOC) in a stable form, which is limited by the stabilization of SOC against microbial mineralization, is largely unknown. In this study, we estimated the C sequestration potential of soils in southeast Germany by calculating the potential SOC saturation of silt and clay parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(116 citation statements)
references
References 81 publications
10
90
2
3
Order By: Relevance
“…Dramatic land-use change, such as shifts from forest to cultivation or grassland, resulted in a completely different soil environment in terms of soil moisture and temperature regimes. It significantly influenced organic matter accumulation and decomposition dynamics [6,64]. Zhao et al [7] reported that soil organic matter (SOM) in about 26 year, when upland was changed to paddy field, had the largest increase of 5.41 ± 3.95 g k −1 in Jiangsu Province of China.…”
Section: Effects Of Land-use Change On Soc Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Dramatic land-use change, such as shifts from forest to cultivation or grassland, resulted in a completely different soil environment in terms of soil moisture and temperature regimes. It significantly influenced organic matter accumulation and decomposition dynamics [6,64]. Zhao et al [7] reported that soil organic matter (SOM) in about 26 year, when upland was changed to paddy field, had the largest increase of 5.41 ± 3.95 g k −1 in Jiangsu Province of China.…”
Section: Effects Of Land-use Change On Soc Contentmentioning
confidence: 99%
“…In addition, SOC is closely related to soil quality, nutrient availability and crop yield [5]. Its decomposition can increase atmospheric CO 2 levels [6], and its sequestration can significantly mitigate global climate change [7]. Changes in land use from native vegetation to agriculture are able to cut down on SOC levels [8,9] and increase atmospheric carbon dioxide concentration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Organic C can be chemically fixed and protected by silt and clay particles through various organo-mineral associations including interactions with aluminosilicates and hydrous oxides (Hassink, 1997;Jastrow et al, 2007;Vogel et al, 2014;Wiesmeier et al, 2014). For example, complexation of organic C with aluminosilicates may occur through multivalent cation bridges between clay platelets and organic C in soils dominated by smectite and/or illite (Jastrow et al, 2007).…”
Section: Fixation Of C On the Surface Of Silt And Clay Particlesmentioning
confidence: 99%
“…Cultivation leads to SOC losses of 30-40% compared to natural or semi-natural vegetation Poeplau et al, 2011). In a regional study, Wiesmeier et al (2013) calculated a mean carbon saturation for Bavarian cropland soils of 53%. Historically, between 32.5 and 35.7 million km 2 of natural vegetation, encompassing forests, woodlands, savannas, grasslands and steppes have been converted to croplands (DeFries et al, 1999).…”
Section: Introductionmentioning
confidence: 99%